GAYA HIDUP REMAJA KOTA (STUDI TENTANG PENGUNJUNG KAFE DI PEKANBARU) - Estika, Ima; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The times are always followed by lifestyle changes that exist in society. The proliferation of cafes that have become one of the icons lifestyle in Pekanbaru lately resulted in people flock to visit, especially in adolescents. Teenagers who tend to like to get together with friends make the cafe as a means to fill his spare time. The cafe has become a part of urban life, always seen a few people whose work relaxing in the cafe to lose track of time. With the times, now to relax in the cafe is no longer just for entertainment or recreational needs alone. However, it has become a lifestyle of teenagers in the city. The phenomenon of lifestyle relax at the cafe that occurs in adolescents is the purpose of this study. In this study, the research subjects amounted to seven people, those who become the subject is teenagers teens who have considered going to cafe as part of their lifestyle. Retrieval of research data by observation, interviews, and documentation. Interviews were conducted in-depth interviews where the researcher asking questions verbally and directly with the subject in full and in-depth. According to the research that has been done can be concluded that the habits of teenagers in Pekanbaru fill his spare time at the cafe because they feel that the cafe has become needs. Facilities such as wi-fi, live music, and they enjoy the game can simply order food and drinks are available in the cafe.Keywords: Lifestyle, Teenagers, Cafe